Pemerolehan dan Pembelajaran Bahasa Kedua pada Anak Usia Prasekolah - Alwi, Said (Saree: Research in Gender Studies, 2021)
Language acquisition is the process of children starting to recognize verbal communication with their environment which is called child language acquisition. Kindergarten levels age are a sensitive period for the development of a child's personality and during this time, several personalities begin to form. The abilities that are formed and develop rapidly at this time include physical development and language skills. Today, learning at the early childhood education and Kindergarten programs levels inaddition to teaching the first language also teaches Arabic and English as a second language. This assumes that children learn foreign languages faster than adults. Learning a foreign language can begin if the child has acquired his first language (his mother tongue). In the process of learning a second language, children will assimilate their mother tongue with the foreign language they are learning. This means that foreign language words that are assimilated by children are not carried out directly but through the intermediary of the mother tongue. The use of the center method is a new paradigm in the field of education and teaching in kindergarten. So far, teachers may only use conventional methods, the result is that children's development in learning is not optimal. Teaching materials are delivered interactively and concretely, by placing students as the center of learning.